Innovative Risk Management Tools in the International Economy: Digitalization, Big Data, and Artificial Intelligence - V. V. Parkhomenko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article examines modern approaches to risk management in international economic relations. The necessity of combining classical methods of risk management (scenario analysis, stress testing) with innovative tools based on digitalization, the use of big data (Big Data), artificial intelligence (AI), and ESG criteria is substantiated. The practices of leading international organizations – the International Monetary Fund and the World Bank – are analyzed. It is shown that current global challenges, in particular the growing debt burden and climate risks, are shaping a new paradigm of risk management. Graphical materials are presented to illustrate relevant trends. The main contribution of the author lies in the systematization of modern risk management methods and the identification of prospects for their application in the international economy.